Short communication: Ecological and faunal complexes of insectivorous mammals of the Republic of Mordovia, Russia - Alexey Andreychev (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Andreychev A. 2020. Short communication: Ecological and faunal complexes of insectivorous mammals of the Republic of Mordovia, Russia. Biodiversitas 21: 3344-3349. In this study, reports that the species composition and occurrence of species in geo-ecological districts are not the same. 12 insectivorous mammals species have been recorded in the territory of Mordovia. The largest number of species in the region belongs to those living in coniferous and broad-leaved forests (42%). In the second place in terms of representation are species widely distributed in several natural areas (33%). They are slightly inferior to the types of taiga fauna (25%). For each geo-ecological district, the features of the rodent fauna are given and rare species are identified. The forest-steppe region of Mordovia is compared in insectivorous mammals fauna with other regions of Russia with different typical faunal complexes.